Interaction between experiment, modeling and simulation of spatial aspects in the JAK2/STAT5 signaling pathway - Friedmann, Elfriede; Cuveland, Rebecca de; Rannacher, Rolf (Model Based Parameter Estimation, 2013)
In this article, we describe how two different approaches, mathematical modeling and quantitative measurements, can be combined to gain new insights on one of the most extensively studied signal transduction pathways, the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. We present two data-based models, which describe the intracellular signaling in a single cell where the signal is transduced from the extracellular domain to the nucleus where STATs regulate gene expression. The two models, one without and one with spatial aspects, have been developed to perform modeling based simulations to find out the way of transport of the STATs in the cytoplasm, and whether cell shape plays a role in this pathway. In this paper we will focus on the parameters of the models, which can be measured with specific techniques in different cell lines, how the unknown parameters are estimated, what the limits of these techniques and how accurate the determinations are.
First online: 03 August 2012
Gesehen am 14.06.2018
Keywords: Konferenzschrift